Buckthorn Leaves and Fruits: A Comparative Study of Their Hepatoprotective Effects in Tetrachloride-Induced Liver Disorders in Rats - Abbas, Rasha Khalid; Elmeged, Lobna Saad Mohammed Abd (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
An overdose of carbon tetrachloride by injection leads to liver damage and massive hepatocellular necrosis, whereas sea buckthorn leaves and fruits have hepatoprotective properties. The aim of this study was to compare the hepatoprotective effects of sea buckthorn leaves and fruits in hepatotoxic rats induced by chlorocarbon. The experiment was carried out in an animal enclosure. Before the start of the experiment, all rats were given a basic diet for one week. The rats were then divided into six groups, each group comprising six rats. The 1st group received only a basic diet for twenty-eight days and served as the rats' normal negative control (C -ve). The other groups of rats (thirty in total) were administered carbon tetrachloride. The groups were divided into five groups, with four groups receiving BL (5% and 10%) and BF (5% and 10%) and one group acting as a control group that suffered from the disease but did not follow the experimental diet. In contrast to the control group (+), all liver values of the rats given different diets showed significant mean reductions. Group "4" (hepatotoxic rats fed ten percent BL) had the highest FI, BWG and ARR compared to the control group (+). For ALP, insignificant differences were found between groups "4" and "6". Mathematically, the best management considering the serum albumin has been documented for group"4" (rats fed on 10% BL) in comparison with control (+) group. Research results indicate its positive effect on the liver and improvement in the condition of liver tissue. It is important to recognise that research on sea buckthorn is still ongoing and further investigation is needed to validate its potential therapeutic applications and determine the appropriate dosages.